Analisis Data Berbentuk Teks dalam Sistem Diagnosis Penyakit dengan Supervised Learning - I Gusti Ngurah Bagus Ferry Mahayudha; Ida Bagus Gede Dwidasmara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
In computer science, text refers to a sequence of characters that can be represented and processed by a computer. It is the basic unit of data for representing human-readable information, such as letters, numbers, symbols, and spaces. In computer programming, text is typically represented as a string of characters. Textual data can be stored in variables, manipulated using various string operations, and displayed to users through input/output operations.Text plays a crucial role in many areas of computer science, including natural language processing, information retrieval, data mining, and text-based communication systems like email, chat applications, and social media. It serves as a fundamental component for storing, analyzing, and processing vast amounts of textual information in various applications.